Lukob - Saniana, Daniel Sunga (2017)
"Lukob (shelter) seeks to question the very foundations of freedom - what constitutes it and who does so? Are we, in our very nature, free just because we aren't confined in an enclosed space? Following Plato's allegory of the cave, Lukob attempts to create a caricature in exploring a person's response to liberation and truth."